2017
DOI: 10.20546/ijcrar.2017.501.014
|View full text |Cite
|
Sign up to set email alerts
|

Workplace Environment and Employee Performance in Selected Brewing Firms in Anambra State

Abstract: Article InfoThe potentials inherent in most brewing firms in Nigeria appeared thwarted by the physical workplace environment in the industry. The broad objective of this study was to determine the relationship between workplace environment and performance of employees in the selected brewing firms in Anambra state, while the study specifically ascertained the type of relationship existing between physical workplace environment and employee commitment. The study was anchored on Dawes and Lofquist (1984) Theory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 4 publications
4
16
0
4
Order By: Relevance
“…Job commitment refers to the total and whole-hearted dedication of academic staff to the policies, initiative, programmes, reforms, and prospects of the university with the willingness to obey and follow all prescribed rules and regulations towards the realization of short-or long-term goals. Employees commitment may also be explained as the strong association linking workers to their organization (Nzewi, Chiekezie, Ekene, Raphael, & Ebuka, 2017;Neyshabor & Rashidi, 2013). To some scholars, organizational commitment includes the following: employee loyalty, emotional affiliation, as well as the cost of leaving an organization (Price & Mueller, 1986;Aleke, Akeke, & Awolusi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Job commitment refers to the total and whole-hearted dedication of academic staff to the policies, initiative, programmes, reforms, and prospects of the university with the willingness to obey and follow all prescribed rules and regulations towards the realization of short-or long-term goals. Employees commitment may also be explained as the strong association linking workers to their organization (Nzewi, Chiekezie, Ekene, Raphael, & Ebuka, 2017;Neyshabor & Rashidi, 2013). To some scholars, organizational commitment includes the following: employee loyalty, emotional affiliation, as well as the cost of leaving an organization (Price & Mueller, 1986;Aleke, Akeke, & Awolusi, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Further, Steger et al (2013) found that perceptions on task significance could be enhanced by redesigning work such that it could be manipulated through interactions with people as task significance enables employees job to have a substantial impact on the lives of other people whether inside or outside the organization environment. Also, studies have consistently demonstrated that task significant work is especially meaningful and positively affects commitment (Allan et al, 2014;Nzewi et al, 2017), as high task significance could serve as a driving force and motivational tool to increase and exert more efforts on the job (Lynton & Pareek, 2000;Omid & Alborz, 2015).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…According to Akinyele (2010), the Nigerian working environment is less supportive. This may be attributed to poverty, corruption, and bad leadership (Nzewi, Augustine, Mohammed, & Godson, 2018). The working conditions of the Nigerian workers have been negatively affected by work intensification, required physical presence at work, and a lack of supportive culture.…”
Section: Working Conditionsmentioning
confidence: 99%